An All-Green Photo-Electrochemical Biosensor Using Microalgae Immobilized on Eco-Designed Lignin-Based Screen-Printed Electrodes to Detect Sustainable Nanoherbicides - Antonacci, Amina; Frisulli, Valeria; Carvalho, Lucas Bragança [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Miranda, Bruno; De Stefano, Luca; Johanningmeier, Udo; Giardi, Maria Teresa; Scognamiglio, Viviana (MDPI, 2023)
Herein, a novel completely green biosensor was designed exploiting both the biological and instrumental components made of eco-friendly materials for the detection of herbicides encapsulated into biodegradable nanoparticles for a sustainable agriculture. Similar nanocarriers, indeed, can deliver herbicides to the correct location, reducing the amount of active chemicals deposited in the plant, impacting the agricultural and food industries less. However, handling measurements of nanoherbicides is crucial to provide comprehensive information about their status in the agricultural fields to support farmers in decision-making. In detail, whole cells of the unicellular green photosynthetic alga Chlamydomonas reinhardtii UV180 mutant were immobilized by a green protocol on carbonized lignin screen-printed electrodes and integrated into a photo-electrochemical transductor for the detection of nanoformulated atrazine. Specifically, atrazine encapsulated into zein and chitosan doped poly-ε-caprolactone nanoparticles (atrazine-zein and atrazine-PCL-Ch) were analyzed following the current signals at a fixed applied potential of 0.8 V, in a range between 0.1 and 5 µM, indicating a linear relationship in the measured dose-response curves and a detection limit of 0.9 and 1.1 nM, respectively. Interference studies resulted in no interference from 10 ppb bisphenol A, 1 ppb paraoxon, 100 ppb arsenic, 20 ppb copper, 5 ppb cadmium, and 10 ppb lead at safety limits. Finally, no matrix effect was observed on the biosensor response from wastewater samples and satisfactory recovery values of 106 ± 8% and 93 ± 7% were obtained for atrazine-zein and atrazine-PCL-Ch, respectively. A working stability of 10 h was achieved.
Keywords: Chlamydomonas reinhardtii; nanoencapsulated-herbicides; photo-electrochemical biosensor; sustainable agriculture